2015
DOI: 10.1016/j.socscimed.2015.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Syndemics of psychosocial problems and HIV risk: A systematic review of empirical tests of the disease interaction concept

Abstract: In the theory of syndemics, diseases co-occur in particular temporal or geographical contexts due to harmful social conditions (disease concentration) and interact at the level of populations and individuals, with mutually enhancing deleterious consequences for health (disease interaction). This theory has widespread adherents in the field, but the extent to which there is empirical support for the concept of disease interaction remains unclear. In January 2015 we systematically searched 7 bibliographic databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
191
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(198 citation statements)
references
References 89 publications
(119 reference statements)
6
191
1
Order By: Relevance
“…The extent to which these and other psychosocial and structural problems co-occur has typically been represented in the literature with the aid of Venn diagrams [13]; correlation matrices demonstrating nonzero, statistically significant values on the off-diagonals [16]; or similar matrices of unadjusted odds ratios [17]. Among the 40 studies included in the systematic review by Tsai & Burns [11], 27 (68%) demonstrated the co-occurrence of psychosocial and structural problems using one of these representations. Such analyses demonstrate that psychosocial and structural problems co-occur in at-risk populations -- thereby supporting one aspect of the theory of syndemics -- but do not necessarily implicate synergy or mutual causality.…”
Section: Modeling Interactions Between Co-occurring Psychosocial and mentioning
confidence: 99%
See 3 more Smart Citations
“…The extent to which these and other psychosocial and structural problems co-occur has typically been represented in the literature with the aid of Venn diagrams [13]; correlation matrices demonstrating nonzero, statistically significant values on the off-diagonals [16]; or similar matrices of unadjusted odds ratios [17]. Among the 40 studies included in the systematic review by Tsai & Burns [11], 27 (68%) demonstrated the co-occurrence of psychosocial and structural problems using one of these representations. Such analyses demonstrate that psychosocial and structural problems co-occur in at-risk populations -- thereby supporting one aspect of the theory of syndemics -- but do not necessarily implicate synergy or mutual causality.…”
Section: Modeling Interactions Between Co-occurring Psychosocial and mentioning
confidence: 99%
“…As summarized by Tsai & Burns [11], most studies in the syndemics literature have not subjected their data to the empirical test described in Eq. (2).…”
Section: Dominant Approaches To Modeling In the Literature On Syndemicsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, nearly one third of the sample had inadequate glycemic control, which was correlated with other markers of disease (e.g., hypertension, depression) and independently associated with substance use, high triglycerides, and unsuppressed HIV viral load. Although the small size of this sample precluded a full analysis of interactions between these potentially syndemic factors [37], our findings suggest that the management of co-occurring chronic conditions is complex and may be challenging for some patients and providers. Our findings also demonstrate the promise of syndemic theory to inform the design of future research that seeks to understand and improve health in this population.…”
Section: Discussionmentioning
confidence: 92%